Peran Strength-Based Parenting Terhadap Academic Buoyancy pada Siswa SMA “X” di Kota Bandung - Grace Erlina Lukas; Marissa Chitra Sulastra (Humanitas (Jurnal Psikologi), 2025)
High school students must have experienced academic difficulties and need skills to overcome them. This study aims to see how strength-based parenting plays a role in academic buoyancy in “X” High School in Bandung City. Strength-based parenting consists of two interrelated aspects, namely strength knowledge and strength use. The measuring instruments used are the Strength-Based Parenting Scale (SBPS) adapted by Hardani, et al. (2022) and the Academic Buoyancy Scale (ABS) adapted by Rohinsa (2019). This study was conducted on active students in grades 10 and 11 at “X” High School in Bandung City, totaling 117 students. Data processing was carried out using simple regression analysis techniques, using the SPSS 25 program. The results obtained were that strength-based parenting did not play a significant role in academic buoyancy in “X” High School students (R2 = 0.019; Sig. = 0.137). However, after further analysis, the aspect of strength use plays a significant role in academic buoyancy (R2=0.035; Sig. = 0.044). In conclusion, strength-based parenting does not play a role in academic buoyancy. The researcher suggests that support be directed to peers or teachers and add mediating variables. Parents of “X” High School students also need to be more involved in the student’s academic process, so that the parenting provided has an impact on helping students overcome academic difficulties.